The Russia-Ukraine crisis: Implications for global and regional food security and potential policy responses - Abay, Kibrom A.; Breisinger, Clemens; Glauber, Joseph W.; Kurdi, Sikandra; Laborde Debucquet, David; Siddig, Khalid (International Food Policy Research Institute, 2022)
This paper analyzes the implications of the Russian-Ukraine crisis on global and regional food security. We start with a global vulnerability analysis to identify most vulnerable regions and countries. The Middle East and North Africa (MENA) region is particularly vulnerable to trade shocks because of its high food import dependence. Thus, we provide descriptive evidence characterizing how food systems and policies impact vulnerability to the price shock in selected MENA countries: Egypt, Sudan, and Yemen. Within these countries, we show that the crisis will differentially impact poor and non-poor households as well as rural and urban households. Although the absolute level of food insecurity may still be higher in rural areas where larger numbers of poor households are located, urban poor are likely to suffer most because of the Russia-Ukraine crisis and associated hikes in food prices, especially in those countries where social protection and food subsidies are missing. On the policy side, we review lessons from previous food crises and identify actions needed to take (and to avoid) to protect most vulnerable countries and households in the short-term while also highlighting long-term policy options to diversify food, fertilizer and energy production and trade.